An explorative study to assess the association between health-related quality of life and the recommended phase II dose in a phase I trial: idarubicin-loaded beads for chemoembolisation of hepatocellular carcinoma. Issue 6 (24th June 2016) - Anota, Amélie; Boulin, Mathieu; Dabakuyo-Yonli, Sandrine; Hillon, Patrick; Cercueil, Jean-Pierre; Minello, Anne; Jouve, Jean-Louis; Paoletti, Xavier; Bedenne, Laurent; Guiu, Boris; Bonnetain, Franck
Abstract : Objectives: The objective of this study was to explore the association between health-related quality of life (HRQoL) and the recommended phase 2 dose in a phase I clinical trial according to the Time to HRQoL deterioration approach (TTD). Setting: This is a phase I dose-escalation trial of transarterial chemoembolisation (TACE) with idarubicin-loaded beads performed in cirrhotic patients with hepatocellular carcinoma. Patients had to complete the EORTC QLQ-C30 HRQoL questionnaire at baseline and at days 15, 30 and 60 after TACE. Participants: Patients aged ≥18 years with HCC unsuitable for curative treatments were evaluated for the study (N=21). Primary and secondary outcome measurements: The primary objective was to determine the maximum tolerated dose (MTD) of idarubicin loaded after a single TACE session. MTD was defined as the dose level closest to that causing dose-limiting toxicity in 20% of patients. HRQoL was the secondary end point. Results: Between March 2010 and March 2011, 9, 6 and 6 patients were included at idarubicin dose levels of 5, 10 and 15 mg, respectively. Calculated MTD of idarubicin was 10 mg. At the 10 mg idarubicin dose, patients presented a longer TTD than at 5 mg, for global health status (HR=0.91 (95% CI 0.18 to 4.72)), physical functioning (HR=0.38 (0.04 to 3.22)), fatigue (HR=0.67 (0.18 to 2.56)) and pain (HR=0.47 (0.05 to 4.24)). Conclusions: These HRQoL results were consistent with the estimated MTD, with a median TTD for global health status of 41 days (21 to NA) at 5 mg, 23 days (20 to NA) at 10 mg and 25 days (17 to NA) at 15 mg. These results show the importance of studying HRQoL in phase I trials. Trial registration number: NCT01040559; Post-results.